Constitutional and legal ideology as a guarantee of the rights and freedoms - Melnikov, Victor Yu.; Omarova, Zuhra S. (Opción, 2019)
The study aims to demonstrate that the formation of a democratic state should be manifested in the trends in the development of public control and increase its impact on the effectiveness of the monitoring functions in relation to the state. The methodological basis of this study is the dialectical method of cognition of social and legal phenomena and concepts in their development and interdependence. As a result, the process of interaction between civil society and the state should be based on ensuring the inviolability of the fundamental social, economic and political rights.